The Implementation of Non-Refoulement Principle in Case of Rohingnya - Utami, Mumpuni Tri (Fakultas Hukum Universitas Negeri Semarang, 2020)
The principle of non-refoulement is a refugee protection framework that prohibits the recipient country to expel the individual concerned to the area where he will experience persecution. Along with developments in international human rights law, the principle of non-refoulement is used as a method of fulfilling and protecting rights that are not interrogated, one of which is the right to be free from torture, cruel, inhuman and degrading behavior. This makes the principle of non-refoulement often applied without exception and discussed to achieve the status of jus cogen, the highest norm in the international legal hierarchy. The increase in asylum seekers is very worrying for the country of Indonesia, because Indonesia is not one of the countries ratifying the 1951 Refugee Convention, and has no obligation to accept asylum seekers, if asylum seekers enter illegally into Indonesia, and can disrupt the stability of Indonesia's defense and security . In general, the state is not asked to allow foreigners to enter its territory, but refugees are an exception to that rule. Refugees are people who are in a very vulnerable situation. They do not get protection from their own country, even often the government itself threatens to persecute them. In such circumstances, the international community makes the necessary efforts to guarantee and ensure that a person's basic rights remain protected and respected. In this international protection status, a person who is in a capacity as a refugee is obliged to get protection for his basic human rights. Rohingya ethnic refugees without citizenship are one example. Torture and discrimination have made them inevitably leave their home countries for centuries. Many of them fled to countries like Indonesia. However, it should be remembered that Indonesia did not ratify the 1956 convention or the 1967 protocol. However, the existence of the principle of non-refoulement caused Indonesia to accept and protect the Rohingya refugees.